Towards an Internet of Things for Health Centers in the Southern Saudi Arabia Region - Mohamed Nadhmi Miladi; Abdel Rahman Hasan; Mohamed Al Ghobiri; Osman Nasr; Ahmed Abelmotlab (Bina Nusantara University, 2021)
The health centers in the village are well equipped in terms of infrastructure. It also has a large group of patients and staff who usually run services such as opening the file and adding data of patients or doctors using the papers and searching between the patient files. This manual job is challenging to do and wastes time. The developed system in the research aims to transform the center into a technology-based center by leaving paperwork in their daily work. The proposed system is considered as the first part of a global and integrated solution based on Internet of Things (IoT) technology. It seeks the enhancement of the Saudi Arabia health system, especially in the current pandemic period. The whole analysis diagrams are realized through the Visual Paradigm tool suite. The patient file management system has three types of modules, including the administrator, doctor, and receptionist. The proposed system provides a computerized patient file management in the health center. It will benefit the small health center and the receptionists who currently depend on the manual system. The proposed system is automated patient file management by integrating hospital information and details and healthcare information of the patients to a central system database. It also provides receptionists an easy way for booking an appointment according to patients’ preference, and they can search and access patients’ information conveniently.